Impact of consumption behaviour on stock-induced material waste. (14th August 2020) - Sharma, Neeta; Vrat, Prem
This paper attempts to examine the impact of consumption behaviour on material waste due to stock-induced consumption phenomenon and introduces an entirely new 'behavioural dimension' to inventory management practices. Stock-induced consumption phenomenon is linked with material waste and a case of water resource wastage due to stock-induced consumption is analysed here from the behavioural perspective. To analyse the behavioural aspects in water resource wastage, a MATLAB simulation program is developed by taking reference of one of the available stock-induced consumption inventory control models. The results obtained in the form of indifference curves reveal the conspicuous increase in water waste due to poor behavioural traits. Based on the results obtained, a concept of behavioural consumption grid is developed to provide insights which can be used in devising policies for reducing stock-induced material waste.